Correlation between ratio of fasting blood glucose to high density lipoprotein cholesterol in serum and non-alcoholic fatty liver disease in American adults: a population based analysis - Jin, Xianjing; Xu, Jing; Weng, Xiaochun (Frontiers in Medicine, 2024)
Background: Based on previous research, elevated fasting blood glucose (FBG) and decreased high-density lipoprotein cholesterol (HDL-C) levels are associated with non-alcoholic fatty liver disease (NAFLD). It is hypothesized that the prevalence of NAFLD may be proportional to the FBG-to-HDL-C ratio (GHR).: In this study, 3842 participants from the National Health and Nutrition Examination Survey (NHANES) (2013-2020) were investigated. Liver steatosis was assessed using vibrationcontrolled transient elastography (VCTE). NAFLD was defined as controlled attenuation parameter (CAP) ≥ 288 dB/m.Results: After adjusting for race, gender, age, diabetes, BMI, moderate activities, uric acid, albumin, ALT, GGT, ALP, total bilirubin and creatinine, multiple logistic regression analysis indicated a positive correlation between GHR and the prevalence of NAFLD (OR=1.22, 95% CI=1.17-1.28).Additionally, multiple linear regression analysis showed a positive correlation between GHR and the severity of liver steatosis according to CAP values (β = 4.97, 95% CI: 4.28, 5.66). According to the subgroup analysis, the correlation was stronger in other race, participants at the age < 50 years old and those with non-diabetes. In this study, a non-linear relationship and saturation effect between GHR and the prevalence of NAFLD was also revealed, characterized by an inverted L-shaped curve, with an inflection point of 7.443. Finally, the receiver operating characteristic (ROC) analysis suggested that the area under the curve (AUC) of GHR (AUC=0.731) significantly exceeded that of FBG and HDL-C.Elevated GHR levels are independently associated with the severity of liver steatosis and the increased prevalence of NAFLD in American adults.